Nitrogen Doped Heat-Treated and Activated Hydrothermal Carbon: Examination of Electrochemical Performance Using Step Potential Electrochemical Spectroscopy. Issue 11 (5th September 2018) - Latham, Kenneth G.; Donne, Scott W.
Abstract : Step potential electrochemical spectroscopy (SPECS) has been applied to nitrogen-doped and non-doped hydrothermal carbons that have been activated or heat-treated at a range of temperatures. The highest surface area achieved was 422 m 2 .g −1 under heat-treatment at 600°C, and 2275 m 2 .g −1 using H3 PO4 chemical activation at 800°C. The heat-treated series reported a maximum capacitance of 84 F.g −1 at 10 mV.s −1, whereas the activated series had a maximum capacitance of 306 F.g −1 at 10 mV.s −1 . SPECS analysis revealed that pseudo-capacitance for the hydrothermal carbon doped with nitrogen was interlinked with the degree of oxygen functionality, and that decreasing the oxygen content of the surface increased the pseudo-capacitance contribution from nitrogen. Pseudo-capacitance also increased with activation from the incorporation of phosphate groups; however, the nitrogen-doped hydrothermal carbons displayed minimal double-layer capacitance (60.6 F.g −1 at 10 mV.s −1 ) despite having reasonable surface areas (1500–1600 m 2 .g −1 ).